THE EFFECTIVENESS OF LEARNING DURING A PANDEMIC COVID-19 - Abdul Mujib; Yuyun Yunita (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
The pandemic Covid-19, which requires everyone, including students to do activities at home, it is easier because of technological advances. The most influential technology in education today is the Internet. The internet allows teachers to provide learning materials without having to meet in person. Teachers can upload learning materials for later access by students. Several internet-based applications and sites are also commonly used by teachers and students to hold face-to-face classes via Whatsapp video calls, Google Clasroom, Zoom Meetings and other online media. Apart from teaching and learning activities, internet-based technology can also be used to support student productive activities. Due to this work from home policy, student activities such as organizations, committees, clubs and so on are hampered. However, by utilizing internet-based applications and sites such as Google Meet, Zoom, Skype and so on, learning activities in the form of meetings and group discussions can run more optimally. Working on group assignments can be easier by using Google Doc where multiple students can edit a document together directly.